Resilience and competitiveness analysis of the crude oil shipping network: identification of crucial nodes and impact of disruptions - Qiu, Weiwei; Zhang, Zhehui; Cui, Mingwei; Zhu, Jishuang (Frontiers in Physics, 2025)
The predominant method of transporting crude oil is by sea, with numerous countries prioritizing energy transportation and ensuring the unimpeded passage of vessels through designated maritime channels. However, the efficacy of international shipping routes is subject to numerous threats and challenges, which have the potential to severely impact or even halt shipping operations. This paper proposes a directed weighted topology model, utilizing ship AIS data and capacity scales, integrating complex network models with social network analysis techniques, to evaluate the operation of the crude oil shipping network under uncertain conditions. The assessment of network topology involves the application of various attack strategies to calculate characteristic indicators of the network and a systematic review of the results. The results indicate that the crude oil shipping network is particularly vulnerable to deliberate attacks, with degree and betweenness attacks demonstrating a higher potential for disrupting the network. It is notable that, upon the occurrence of a certain level of attack intensity, specific nodes (or channels) may become inoperable, necessitating the selection of alternative routes or reassessment of supply sources. Furthermore, this research establishes a competitiveness and security index to quantitatively identify the crucial nodes within the crude oil shipping network. The findings of this study are of considerable practical and strategic significance, insofar as they facilitate a more profound comprehension of the resilience of the maritime energy transportation framework, and of the improvement of its role in supporting national economic and social development.